Eden within Eden: Oregon's utopian heritage - Kopp, James J. (Oregon State Univ. Press, 2009)
Introduction: Oregon as Eden -- Eden and utopia : background and boundaries -- The American utopian tradition -- The dawn of utopia in Oregon : the Aurora Colony -- Seeking the ideal community in Oregon in the 1880s and 1890s -- No place -- Cooperation in Oregon in the early twentieth century -- From cooperation to survival in the twentieth century -- Rediscovering utopia : the new pioneers of the late 1960s -- The dream continues : from the 1970s to the twenty-first century -- The dark side of utopia -- Conclusion: Oregon as utopia